Causes of academic dropout in higher education in Andalusia and proposals for its prevention at university: A systematic review - de la Cruz-Campos, Juan-Carlos; Victoria-Maldonado, Juan-José; Martínez-Domingo, José-Antonio; Campos-Soto, María-Natalia (Frontiers in Education, 2023)
Introduction: One of the main problems facing the university system is the high student dropout rate due to a number of variables, accentuated by the Covid-19 pandemic. This is a problem not only in Spanish universities but is prevalent worldwide. It is therefore important to understand and analyze the underlying reasons for dropout so that it can be addressed and mechanisms implemented to limit dropout in higher education to the greatest extent possible. Method: A systematic review was carried out summarizing the results of studies and reports on university dropout in Spain and specifically in the universities of the Autonomous Community of Andalusia. The review was conducted in accordance with the PRISMA statement by searching the scientific databases Scopus and Web of Science, limiting the search to articles published between 2010 and 2022. Results: The main publications in both Spain and the Autonomous Community of Andalusia were identified. The review included the main causes of university dropout indicated in each of the selected studies and the proposals to reduce it, including educational policies, the rise of distance education, academic failure in basic educational stages, and social, personal, psychological and economic variables. Conclusions: There is a lack of research on university dropout, with only 25% of Spanish universities having carried out research on this subject in the last 12 years. The studies analyzed conclude that the most frequent causes of university dropout are associated with low academic performance, poor social support in the new academic environment, low socio-economic status, pessimism and lack of motivation, together with other less significant factors such as poor relationships with teachers, lack of vocation, work incompatibility and previous academic performance. Further research on the causes of university dropout and its prevention is needed both before university entrance, by providing meaningful information to secondary school students, and during the university stay, through institutional and teaching policies that improve family support and social roots, produce positive academic experiences, favor associationism and encourage activities that improve planning and time management, together with cognitive learning strategies, motivational strategies and the use of advanced learning materials (such as ICT tools).